2012
DOI: 10.1088/0004-637x/753/1/64
|View full text |Cite
|
Sign up to set email alerts
|

CHEMICAL ABUNDANCES OF THE MILKY WAY THICK DISK AND STELLAR HALO. I. IMPLICATIONS OF [α/Fe] FOR STAR FORMATION HISTORIES IN THEIR PROGENITORS

Abstract: We present the abundance analysis of 97 nearby metal-poor (−3.3 < [Fe/H] < −0.5) stars having kinematic characteristics of the Milky Way (MW) thick disk and inner and outer stellar halos. The high-resolution, high-signalto-noise optical spectra for the sample stars have been obtained with the High Dispersion Spectrograph mounted on the Subaru Telescope. Abundances of Fe, Mg, Si, Ca, and Ti have been derived using a one-dimensional LTE abundance analysis code with Kurucz NEWODF model atmospheres. By assigning m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
131
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(150 citation statements)
references
References 113 publications
16
131
3
Order By: Relevance
“…Previous studies have also reported the detection of α-element abundance differences in metal-poor stars, with some making selections specifically in Mg, as performed here (Nissen & Schuster 2010;Navarro et al 2011;Ishigaki et al 2012;Sheffield et al 2012;Jackson-Jones et al 2014;Hawkins et al 2015), albeit with fewer stars. The advantage of our study is that we rely on a large sample of stars that have homogeneously determined abundances for many chemical species.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Previous studies have also reported the detection of α-element abundance differences in metal-poor stars, with some making selections specifically in Mg, as performed here (Nissen & Schuster 2010;Navarro et al 2011;Ishigaki et al 2012;Sheffield et al 2012;Jackson-Jones et al 2014;Hawkins et al 2015), albeit with fewer stars. The advantage of our study is that we rely on a large sample of stars that have homogeneously determined abundances for many chemical species.…”
Section: Discussionmentioning
confidence: 80%
“…A commonly used strategy is to rely on kinematical definitions to separate stars into populations (Venn et al 2004;Reddy et al 2006;Ruchti et al 2011;Ishigaki et al 2012Ishigaki et al , 2013. Unfortunately, this is fraught with several difficulties, not least that it requires that the necessary kinematical data are in hand and of sufficient quality to provide meaningful discrimination.…”
Section: Introductionmentioning
confidence: 99%
“…Among the different proposed processes that could produce this abundance flattening, we wish to mention: (i) large-scale processes of angular momentum transport that produce a mix of gas abundances, including radial gas flows (e.g., Lacey & Fall 1985;Goetz & Koeppen 1992;Portinari & Chiosi 2000;Schönrich & Binney 2009;Spitoni & Matteucci 2011), resonance scattering with transient spiral density waves (Sellwood & Binney 2002), and the overlap of spiral and bar resonances (Minchev et al 2011); (ii) minor mergers and captures of or perturbations by satellite galaxies that increase the metal content in the outer regions (Quillen et al 2009;Bird et al 2012); (iii) a nonlinear Schmidt-Kennicutt law that is able to trigger a highly efficient star formation process at these distances (e.g., Esteban et al 2013); (iv) a spatial association of the flatter area with gas located in the thick disk, which is known to have different metallicity patterns (e.g., Neves et al 2009;Ishigaki et al 2012); (v) a plateau of the gas abundance in the intergalactic medium due to the cosmological evolution of galaxies; and the subsequent pollution of metals (Sánchez et al, in prep. ); Stellar radial migration has also been proposed as a possible cause for the flattening of the metallicity gradients for stellar populations in spiral galaxies (e.g., Roškar et al 2008b,a).…”
Section: The Flattening Of the Abundance Gradient In The Outer Regionsmentioning
confidence: 99%
“…Figure 8 compares mean abundances of the Boötes I stars and field halo stars in the metallicity range of −3.0 < [Fe/H] < −2.0. To minimize systematic errors in the abundance comparison, eight halo giants (T eff < 5000 K and log g < 3.0, including one of the comparison stars HD 85773) from Ishigaki et al (2012Ishigaki et al ( , 2013 are only considered for the field halo sample. In their work, the adopted 1D-LTE abundance analysis technique and the line list are the same as in this work.…”
Section: Comparison With the Field Mw Halomentioning
confidence: 99%